Sputter-Coated TiO2 Films as Passivation and Hole Transfer Layers for Improved Energy Conversion with Solar Fuel WO3/CuWO4 Photoanodes - Escaliante, Lucas Caniati [UNESP]; Azevedo Neto, Nilton Francelosi; Mendoza, Hervin Errol; Xiao, Chengcan; Kandel, Rajesh; da Silva, Jose Humberto Dias [UNESP]; Osterloh, Frank E. (American Chemical Society (ACS), 2024)
Atomic-layer-deposited (ALD) “leaky” TiO2 has gained interest as a charge-selective protection layer for semiconductor solar fuel electrodes. Here, the use of sputter-deposited TiO2 layers as hole-selective contacts for WO3/CuWO4 type-2 heterojunction water oxidation photoanodes is demonstrated for the first time. TiO2 protection layers with varying thicknesses (2 to 128 nm) were deposited by using the radio frequency (RF) magnetron sputtering technique. The resulting TiO2 films are amorphous as evidenced by Raman spectroscopy and powder X-ray diffraction (XRD). Photoelectrochemical scans and vibrating Kelvin probe photovoltage spectroscopy show that 2-8 nm TiO2 layers nearly double the photocurrent to 0.97 mA cm-2 under AM1.5 illumination (19% AQE at 350 nm), increase the surface photovoltage signal by 25%, and increase the WO3/CuWO4 effective band gap. These outcomes can be attributed to the selectivity of TiO2 for photoholes. Additionally, SPV data suggest that TiO2 overlayers suppress copper-based surface recombination defects. Reduced photocurrents and photovoltages are measured in thicker TiO2 films (16 to 128 nm) as a result of an increasing hole transfer resistance and because of light shading effects according to photoaction spectra. The TiO2 films also improve the stability of the WO3/CuWO4 photoelectrodes, allowing nearly constant O2 evolution over 3 h after an initial 20-35% loss. Overall, this work establishes RF magnetron sputtering as a useful method to install amorphous TiO2 passivation layers for improved WO3/CuWO4 solar fuel photoelectrodes. Furthermore, we show how the combination of PEC and SPV measurements provides insight into the function of the TiO2 coatings.
Keywords: CuWO4; photoanode; photoelectrochemistry; RF magnetron sputtering; surface photovoltage spectroscopy; TiO2; water splitting; WO3